(untitled) (Al-Academy, 2022)
Theatrical art, from (Plato) to (Heidegger), passing through (Husserl) and (Husserl) has propagated the parallel relations between the overlapping formal patterns in the world of hypotheses crowded with diaspora and scattering, leading to the manifestations of implicit meaning in the intellectual and aesthetic discourse, through the deconstructive pattern that restructures The aesthetic image according to the aesthetic data to be employed, so the effectiveness of the deconstructive system had an important role in authorizing the Ghanaian logic and continuity on which the Western meta meaning was based, and the artistic scene was subjected to it in line with literature and art to be able to pay attention to the achievement and clarify it in a more accurate, broader and more comprehensive way than it was, The deconstructive reading had its dominant equations, and its main lines in (writing, impact and difference), so this research stopped at those lines and their functional formats, which are located in four chapters, namely:The first chapter: the methodological framework, and it contained the research problem, the need for it, the importance of the research, the objectives of the research, and the limits of the research. The second chapter: included a theoretical framework that contained two sections: the first: the strategy of deconstruction from concept to work, and the second: the aesthetic employment of deconstruction in the experiences of the world theater.As for the third chapter: it came with the procedural framework, which includes the research methodology, the research community and the research sample, and the fourth chapter: includes the results and their discussion, and the conclusions, including:1. The Iraqi director, through the effectiveness of the deconstructive formats, employed the political, intellectual and social crises after deciphering many of the writing codes and mechanisms.2. The deconstructive consistency made the presentation in front of opposing pairs that can be occupied in understanding and reading theatrical discourse in the performances, production and reading